If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2m) + -4(2m + 1) = 13 Remove parenthesis around (2m) 6 * 2m + -4(2m + 1) = 13 Multiply 6 * 2 12m + -4(2m + 1) = 13 Reorder the terms: 12m + -4(1 + 2m) = 13 12m + (1 * -4 + 2m * -4) = 13 12m + (-4 + -8m) = 13 Reorder the terms: -4 + 12m + -8m = 13 Combine like terms: 12m + -8m = 4m -4 + 4m = 13 Solving -4 + 4m = 13 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4m = 13 + 4 Combine like terms: -4 + 4 = 0 0 + 4m = 13 + 4 4m = 13 + 4 Combine like terms: 13 + 4 = 17 4m = 17 Divide each side by '4'. m = 4.25 Simplifying m = 4.25
| 7/9d-1/2=1/5 | | 8(2x-6)=-112 | | -33=-5(6n+3) | | 10(y-8)=-30 | | 11x+2x=91 | | 3(n-7)=-7 | | 14-2(4x-8)=6 | | 6(x+3)+6=42 | | 2x+3=5x+8 | | 5r^2-20r-9=6 | | 3w(11w+8)= | | 5r^2-20r-9=0 | | 13.62+.13(x+3)=14.37-.09x | | xsquare(x+5)(x-5)=0 | | 1600x=20 | | 3y+17=62 | | y+19=192 | | f(-6)=7-2x | | 4x+14=5x | | 2x=6(2x-2)-5 | | 13.62+.13(x+3)=14.37+.09x | | 3(3+1)=(9-2x) | | 6n=(n+5) | | 30=-8x+2(x-6) | | y=mx+bfindx | | x^1/4=2 | | 5x-15=2x+20 | | 90+3+x+x-8=180 | | 10n-0.75=0.1n-0.375 | | 2-7g=2-g | | 2e^3x-9=0 | | 12a=3a+2.5a+a |